Discovery of a novel chalcone derivative inhibiting CFTR chloride channel via AMPK activation and its anti-diarrheal application - Chamnan Yibcharoenporn; Phakawat Chusuth; Chanon Jakakul; Thanyada Rungrotmongkol; Warinthorn Chavasiri; Chatchai Muanprasat (Elsevier, 2019)
Secretory diarrhea is one of the most common causes of death world-wide especially in children under 5 years old. Isoliquiritigenin (ISLQ), a plant-derived chalcone, has previously been shown to exert anti-secretory action in vitro and in vivo by inhibiting CFTR Cl− channels. However, its CFTR inhibition potency is considerably low (IC50 > 10 μM) with unknown mechanism of action. This study aimed to identify novel chalcone derivatives with improved potency and explore their mechanism of action. Screening of 27 chalcone derivatives identified CHAL-025 as the most potent chalcone analog that reversibly inhibited CFTR-mediated Cl− secretion in T84 cells with an IC50 of ∼1.5 μM. As analyzed by electrophysiological and biochemical analyses, the mechanism of CFTR inhibition by CHAL-025 is through AMP-activated protein kinase (AMPK), a negative regulator of CFTR activity. Furthermore, Western blot analyses and molecular dynamics (MD) results suggest that CHAL-025 activates AMPK by binding at the allosteric site of an upstream kinase calcium/calmodulin-dependent protein kinase kinase β (CaMKKβ). Interestingly, CHAL-025 inhibited both cholera toxin (CT) and bile acid-induced Cl− secretion in T84 cells and prevented CT-induced intestinal fluid secretion in mice. Therefore, CHAL-025 represents a promising anti-diarrheal agent that inhibits CFTR Cl− channel activity via CaMKKβ-AMPK pathways. Keywords: Diarrhea, CFTR, Chalcone, AMPK, Chloride secretion